EFEKTIVITAS BUBUK BIJI PEPAYA (Carica Papaya Linnaeaus) SEBAGAI LARVASIDA ALAMI TERHADAP KEMATIAN LARVA AEDES AEGYPTY TAHUN 2015 - Iwan Iskandar; Hevi Horiza; Nanang Fauzi (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2017)
Papaya seeds are excellent to be used as a repellent larvae of Aedes aegypti because of the toxins contained in papaya seeds called alkaloid karpaina. The research objective was to determine the effectiveness of papaya seeds powder as Aedes aegypti larvicides. This type of research is True Experiment with Posttest Only Control Group research design, using five treatments (4 grams, 8 grams, 12 grams, 16 grams and 20 grams) and one control. Objects that are used as many as 600 larvaes of Aedes aegypti. If the papaya seeds powder in a simple processsuch as drying and grinding. Each treatment contains 50 larvaes and by doing 2 times repeatedly. The results of data analysis on the number of dead larvaes at a dose trending dead at the lowest possible total percentage of 22% at a dose of 4 grams and the highest percentage of 97% at a dose of 20 grams. The analysis result of one-way ANOVA for the number of differences in the number of dead larvaes, with the value obtained sig. = 0.000, so that ? <? (0.05) means that there is a significant influence on differences in doses of papaya seeds powder solution used against the death of Aedes aegypti larvaes. The control of Aedes aegypti larvaes using papaya seeds powder can be done by puttingthe powder of papaya seeds as much as 20 grams per 10 liters of water for 24 hours of treatment.